Pemahaman Masyarakat Gampong Cot Trieng terhadap Taklik Talak Pasca Akad Nikah dalam Perspektif KHI - Ridhayani Ridhayani; Hasnul Arifin Melayu; Muhammad Husnul (Lembaga Yasin AlSys, 2026)
Although taklik talak has been normatively regulated in the Kompilasi Hukum Islam as an instrument for protecting wives’ rights in marriage, community practice and understanding of its implementation still show various problems. Studies that specifically discuss community understanding of taklik talak after the marriage contract, particularly in the practice where the sighat taklik talak is not recited but signing in the marriage book is still carried out, remain limited, especially in the Aceh region. This study aims to analyze the understanding of the people of Gampong Cot Trieng regarding taklik talak after the marriage contract from the perspective of the Kompilasi Hukum Islam and to identify the factors affecting this low level of understanding. This study employed a qualitative approach with a descriptive-analytical empirical juridical method. Data were collected through interviews, observation, and documentation involving 15 participants consisting of gampong officials and married couples with marriage durations of 5, 10, and 20 years, who were selected using a purposive sampling technique. The data were analyzed by relating the empirical findings to legal awareness theory. The findings showed that the practice of taklik talak in Gampong Cot Trieng was generally carried out only through signing without recitation of the sighat taklik talak, so that taklik talak was understood merely as an administrative formality rather than as a binding legal agreement. The level of public legal awareness remained at a minimal knowledge stage and had not reached substantive understanding, which was influenced by the lack of institutional socialization and the dominance of ritual social practices. These findings emphasize the importance of a sociological approach in assessing the effectiveness of Islamic family law norms and provide practical implications for strengthening the role of the Office of Religious Affairs and gampong officials in improving public understanding of the substance of taklik talak.